Beach Drainage System: A Comprehensive Review of a Controversial Soft-Engineering Method - Piera Fischione; Davide Pasquali; Daniele Celli; Carmine Di Nucci; Marcello Di Risio (Journal of Marine Science and Engineering, 2022)
The beach drainage can be included among the soft engineering methods aimed to counteract the shoreline retreat related to the sediment redistribution along the beach profile. The idea that the groundwater table plays a role in the mobilization of the sediment grains underlies the application of the beach drainage system (BDS) as a tool able to modify the natural dynamics of groundwater table at sandy beaches. Indeed, BDS consists of a series of alongshore buried drains aimed to lower the groundwater table. Due to the drainage, the thickening of the layer of dry sand makes the solid grains less prone to be mobilized by the action of the waves at the swash zone, where interaction phenomena between the percolating and the incoming water lens take place. This tool had a troubled history. Its first applications were encouraging. Since then, controversial performances of both experimental and prototype scale experiences have been observed around the world. This paper aims to present an up-to-date full review of the studies and experiments carried out so far, in order to provide the reader with a complete perspective on its strength and weakness as well as open challenges to be faced in the near future.